Causes and Consequences of Truancy Among in School Adolescents in Oyo North Senatorial District Nigeria - Foluke Nike Bolu Steve; Rasaq Abimbola Fadipe; Olajide Charles Kayode (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2022)
Background:  The need to increase the mastery of Information and Computer Technology (ICT) in teaching and learning activities is essential and urgent, especially during the COVID-19 pandemic. The PowerPoint application is a popular application for creating learning content, but most teachers are only at the level of "powerpointers". SMK Negeri Windusari, as a vocational high school, requires an increase in the level of its educators, namely those who can increase learning outcomes, one of which is by developing multimedia content based on PowerPoint. This training was in collaboration with UNIMMA Informatics Engineering. It was attended by twenty-four teachers starting with a pre-test and ending with a post-test to measure the level of success. Contribution: Improving the quality of content to support learning outcomes. Method:  The training on the use of ICT for learning begins with observation through a pre-test and ends with a presentation of the training results, and then measures progress using a post-test. Results:  The results of the training showed that most of the participants showed improvement. Conclusion:  This training is expected to be sustainable as a form of support for improving the quality of learning content.